Solid pseudopapillary epithelial neoplasm: a rare cause of intractable abdominal pain in young women - Shreya Hegde; Vinitha Samartha; Philipose Thoppil Reba (International Journal of Medical Research and Review, 2017)
Solid pseudopapillary epithelial neoplasms of the pancreas are extremely rare and usually affect young women. It distinguishes itself from other pancreatic neoplasms with its low malignant potential. These tumors have a long asymptomatic period and are usually detected when they have grown to a very large size. We report a case of a 16 year old female patient who presented with intractable abdominal pain since past 1 month. A provisional diagnosis of Solid Pseudopapillary Epithelial Neoplasm was made on CT scan and confirmed by biopsy and histopathology. Early preoperative recognition of this tumour and confirmation by histopathology is emphasized because complete resection usually results in cure.